Survey on drug utilization in outpatient treatment of type 2 diabetes: A cross-sectional study at a medical center, Vietnam, 2024 - 2025 - Kieu, Le Thi Thuy; Ngan, Doan Thi Kim; Duong, Huynh Hai; Thuy, Nguyen Thi Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: The increasing prevalence of type 2 diabetes rates emphasizes the need to assess outpatient drug utilization patterns and potential drug-drug interaction (DDIs). Objective: This study aimed to determine the antidiabetic drug utilization patterns, assess the prevalence of potential drug-drug interactions, and analyze factors associated with DDIs in outpatient prescriptions for type 2 diabetes mellitus (T2DM). Materials and methods: A cross-sectional descriptive study was conducted using retrospective data from outpatients with T2DM treated at the District 5 Medical Center, Ho Chi Minh City, between August 2024 and February 2025. Prescriptions were analyzed for drug utilization patterns and screened for potential DDIs using Drugs.com and Medscape databases. Patient demographics and comorbidities were assessed as determinants of DDIs. Results: A total of 415 outpatient prescriptions were reviewed. The male-to-female ratio was 1:1.20, with more than half of the patients aged ≥ 65 years (52.8%). Dual therapy predominated (67.7%), and biguanides were prescribed in 90.8% of cases. Potential DDIs were identified in 68.9% of prescriptions via Drugs.com and 74.7% via Medscape, the majority classified as moderate. Hypertension, cardiovascular disease, renal impairment, and biguanide use were significantly associated with an increased risk of DDIs. Conclusion: Antidiabetic prescribing at the district level is characterized by widespread use of dual therapy and a high prevalence of potential DDIs. Strengthening clinical pharmacy services and implementing systematic prescription reviews are essential to optimize T2DM management and minimize the risks associated with drug interactions.